2017
DOI: 10.1080/17429145.2017.1392627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular response of gall induction by aphid Schlechtendalia chinensis (Bell) attack on Rhus chinensis Mill

Abstract: Horned gall is named after its shape of irregular diamond, and is induced by the fluid-feeding aphid Schlechtendalia chinensis (Bell) attacks on the leaflets that are located in the branchlets of Rhus chinensis Mill., which is enriched in gallotannin and can be widely used in medicine and the food industry. To explain the molecular mechanism of gall development, we performed transcriptome analysis by Illumina deep sequencing and digital gene expression of four tissues, including galls, leaves that grew on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Plant hormone signal transduction (ko04075) and the biosynthesis of secondary metabolites (ko01110) were the most common KEGG pathways detected ( Figure S2). , and the two pathways have been previously found to be significantly involved in abiotic stress response [26][27][28][29]. Moreover, the leaf-specifically enriched KEGG terms detected were those related to the photosynthetic apparatus of the plant leaf, such as Photosynthesis (ko00195) and Photosynthesis -antenna proteins (ko00196).…”
Section: Functional Annotation Of Degs Sets In the Three Accessions Omentioning
confidence: 92%
“…Plant hormone signal transduction (ko04075) and the biosynthesis of secondary metabolites (ko01110) were the most common KEGG pathways detected ( Figure S2). , and the two pathways have been previously found to be significantly involved in abiotic stress response [26][27][28][29]. Moreover, the leaf-specifically enriched KEGG terms detected were those related to the photosynthetic apparatus of the plant leaf, such as Photosynthesis (ko00195) and Photosynthesis -antenna proteins (ko00196).…”
Section: Functional Annotation Of Degs Sets In the Three Accessions Omentioning
confidence: 92%
“…Plant hormone signal transduction (ko04075) and the biosynthesis of secondary metabolites (ko01110) were the most common KEGG pathways detected ( Figure S2). , and the two pathways have been previously found to be significantly involved in abiotic stress response [26][27][28][29]. Moreover, the leaf-specifically enriched KEGG terms detected were those related to the photosynthetic apparatus of the plant leaf, such as Photosynthesis (ko00195) and…”
Section: Differential Gene Expression After Alkali-salt Treatmentmentioning
confidence: 94%
“…Indeed, a transcriptome analysis of psyllid galls on the Hawaiian Metrosideros polymorpha showed that auxin response genes were upregulated in galls [96]. In Rhus chinensis and Rhus javanica gall formation, the genes involved in auxin and abscisic acid (ABA) metabolic and signal transduction pathways are significantly activated [97,98].…”
Section: Changes In Plant Hormonal Regulation During Gall Developmentmentioning
confidence: 99%
“…Tannins are crucial in the protection of host plants and gall-inducing insects from herbivory. Aphis galls on Rhus chinensis accumulate gallotannin, and genes involved in gallotannin biosynthesis [99], gallic acid synthesis [98], and lignin biosynthesis [97] have been identified. In the developing gall of the chestnut gall wasp, Dryocosmus kuriphilus, on the Chinese chestnut, Castanea mollissima, the expression of genes related to metabolic processes, such as phenylpropanoid biosynthesis, secondary metabolism, and plant-pathogen interactions, was altered compared to that of non-infested leaves [100].…”
Section: Changes In the Expression Patterns Of Genes Involved In The Biosynthesis Of The Metabolic Process During Gall Formationmentioning
confidence: 99%